Elimination of Carryover Contamination in Real-Time Reverse Transcriptase Loop-Mediated Isothermal Amplification for Rapid Detection of the SARS-CoV-2 Virus in Point-of-Care Testing - Quyen, Than Linh; Vinayaka, Aaydha Chidambara; Golabi, Mohsen; Ngoc, Huynh Van; Bang, Dang Duong; Wolff, Anders (Frontiers in Cellular and Infection Microbiology, 2022)
Loop-mediated isothermal amplification (LAMP) is being used as a robust rapid diagnostic tool to prevent the transmission of infectious diseases. However, carryover contamination of LAMP-amplified products originating from previous tests has been a problem in LAMP-based bio-analytical assays. In this study, we developed a Cod-uracil-DNA-glycosylase real-time reverse transcriptase LAMP assay (Cod-UNG-rRT-LAMP) for the elimination of carryover contamination and the rapid detection of SARS-CoV-2 in point-of-care (POC) testing. Using the Cod-UNG-rRT-LAMP assay, the SARS-CoV-2 virus could be detected as low as 2 copies/µl (8 copies/reaction) within 45 min of amplification and 2.63 ± 0.17 pg (equivalent to 2.296 × 109 copies) of contaminants per reaction could be eliminated. Analysis of clinical SARS-CoV-2 samples using the Cod-UNG-rRT-LAMP assay showed an excellent agreement with a relative accuracy of 98.2%, sensitivity of 97.1%, and specificity of 95.2% in comparison to rRT-PCR. The results obtained in this study clearly demonstrate the feasibility of the use of the Cod-UNG-rRT-LAMP assay for applications toward the POC diagnosis of SARS-CoV-2 and on-site testing of other pathogens.